Human Induced Pluripotent Cell-Derived Sensory Neurons for Fate Commitment of Bone Marrow-Derived Schwann Cells: Implications for Remyelination Therapy. (14th September 2016) - Cai, Sa; Han, Lei; Ao, Qiang; Chan, Ying-Shing; Shum, Daisy Kwok-Yan
Abstract: Strategies that exploit induced pluripotent stem cells (iPSCs) to derive neurons have relied on cocktails of cytokines and growth factors to bias cell-signaling events in the course of fate choice. These are often costly and inefficient, involving multiple steps. In this study, we took an alternative approach and selected 5 small-molecule inhibitors of key signaling pathways in an 8-day program to induce differentiation of human iPSCs into sensory neurons, reaching ≥80% yield in terms of marker proteins. Continuing culture in maintenance medium resulted in neuronal networks immunopositive for synaptic vesicle markers and vesicular glutamate transporters suggestive of excitatory neurotransmission. Subpopulations of the derived neurons were electrically excitable, showing tetrodotoxin-sensitive action potentials in patch-clamp experiments. Coculture of the derived neurons with rat Schwann cells under myelinating conditions resulted in upregulated levels of neuronal neuregulin 1 type III in conjunction with the phosphorylated receptors ErbB2 and ErbB3, consistent with amenability of the neuritic network to myelination. As surrogates of embryonic dorsal root ganglia neurons, the derived sensory neurons provided contact-dependent cues to commit bone marrow-derived Schwann cell-like cells to the Schwann cell fate. Our rapid and efficient induction protocol promises not only controlled differentiation of human iPSCs into sensory neurons, but also utility in the translation to a protocol whereby human bone marrow-derived Schwann cells become available for autologous transplantation and remyelination therapy.